2019
DOI: 10.1007/s42452-019-0558-5
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of structural aesthetics in architecture case study: Taj-Ol-Molk Dome, Jāmeh Mosque of Isfahan, Iran

Abstract: The role of structure has been always considered essential in understanding the architecture. In the historical buildings of Iran, the function of structural elements follows the general form of the building. In this study, the modern structural analysis of historical building aimed at discovering the deep knowledge of experienced and skilled constructors in their works, developing the modern structural theories, and establishing modern solutions for strengthening of structural elements. Taj-Ol-Molk Dome was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…They act as a surface, akin to a layered canvas, which serves as a bridge between the interior and exterior of a building. The study confirmed that classical architectural facades were characterized by a rich abundance of intricate details and distinctive elements (Sadeqi et al, 2019), (Morvan and Thibert, 2002), (Chatzikonstantinou and Sariyildiz, 2017), (Riccobono, 2014).These facades employed symmetry and balance to distribute forces in accordance with the mathematical principles governing gravity. In the context of Gothic architecture, facades took on a sculptural form, featuring walls crafted from carved stone, sculptures, and embellishments around openings.…”
Section: The Evolution Of Architectural Facadessupporting
confidence: 69%
See 4 more Smart Citations
“…They act as a surface, akin to a layered canvas, which serves as a bridge between the interior and exterior of a building. The study confirmed that classical architectural facades were characterized by a rich abundance of intricate details and distinctive elements (Sadeqi et al, 2019), (Morvan and Thibert, 2002), (Chatzikonstantinou and Sariyildiz, 2017), (Riccobono, 2014).These facades employed symmetry and balance to distribute forces in accordance with the mathematical principles governing gravity. In the context of Gothic architecture, facades took on a sculptural form, featuring walls crafted from carved stone, sculptures, and embellishments around openings.…”
Section: The Evolution Of Architectural Facadessupporting
confidence: 69%
“…In the context of deconstructivism architecture, facades underwent a transformation to embody the ideology of breaking free from traditional constraints. This led to the creation of facades with multiple layers (Sadeqi et al, 2019), (Radić et al, 2010), (Soycan and Soycan, 2019). These facades were fragmented, concealed, fragmented, incomplete, and featured Technological advances in structural solutions and new materials (Two International Finance Centre).…”
Section: The Evolution Of Architectural Facadesmentioning
confidence: 99%
See 3 more Smart Citations